Uji Mulsa Organik Terhadap Gulma Dan Produksi Kacang Hijau (Phaseolus radiatus L.) - Martha Aulia Reyndi; Chairul Chairul; Zuhri Syam (Jurnal Biologi Universitas Andalas, 2015)
We experimentally studied the effect of organic mulches on weeds and yield of green beans (Phaseolus radiatus L.) have been conducted at green house and Laboratory of Plant Ecology, Departement of Biology, Faculty of Natural Sciences, Andalas University, Padang, from January to May 2014. The aims of this study were to determine the effect of different mulches (Mikania micrantha and Tithonia diversifolia) on weeds and yield of green beans. The experiment used nested design with eight treatments and three replications. The first factor (factor A) was two kinds of mulch (i.e Mikania micrantha and Tithonia diversifolia). While the second factor (factor B) was the given doses of mulch (i.e 0 g/polybag, 300 g/polybag, 600 g/polybag and 900 g/polybag). The results showed that Mikania micrantha mulch gave the stronger effect to reduce weed numbers. Mikania micrantha mulch on 900 g/polybag increased plant height and Mikania micrantha mulch on 300 g/polybag increased seed yield. Whereas Tithonia diversifolia mulch on 600 g/polybag increased plant height and the number of primary branches and Tithonia diversifolia mulch on 300 g/polybag increased seed yield.